Entrepreneurial leadership, performance, and sustainability of micro-enterprises in Malaysia - Al Mamun, Abdullah; Ibrahim, Mohamed Dahlan; Yusoff, Mohd Nor Hakimin; Fazal, Syed Ali (2018)
This study probed into the impact of entrepreneurial leadership dimensions (i.e., responsibility, accountability, analytical thinking, and emotional intelligence) on the performance and sustainability of micro-enterprises in Kelantan, Malaysia, through the lens of resource-based view (RBV) theory. Through the implementation of a cross-sectional design, data were randomly gathered from 403 micro-entrepreneurs whose names appeared in the list of low-income households registered under “Majlis Amanah Rakyat” Kelantan and “Majlis Agama Islam Dan Adat Istiadat” Kelantan. The quantitative data were collected during structured interview sessions held between September and December 2017. The findings of the study revealed that the aspects of responsibility, accountability, and emotional intelligence exhibited significantly positive effects on micro-enterprise performance; while accountability, analytical thinking, and micro-enterprise performance displayed a significantly positive influence on sustainability among micro-enterprises owned by low-income households in Kelantan, Malaysia. The outcomes further portrayed a significant mediating effect of micro-enterprise performance on the correlations of responsibility, analytical thinking, and emotional intelligence with micro-enterprise sustainability. The outcomes of this study extend the scope of RBV theory and simultaneously enhance our understanding pertaining to leadership, performance, and sustainability interplay, particularly within the context of micro-enterprises in emerging economies. As such, it is recommended that the government of Malaysia formulate and to adopt policies that promote varied entrepreneurial-leadership-related traits among budding micro-entrepreneurs, which may not only boost sustainability performance among firms, but also encourage low-income household heads to actively engage in more entrepreneurial activities.